Leisure lifestyles : organizing everyday life for fun and fulfillment - Stebbins, Robert A. (Emerald points., 2021)
Acknowledging that the challenge facing social science is how to inject some order into the common-sense notion of leisure lifestyles, this book, written by a major player in the field of leisure, considers how to turn the study of both serious and casual leisure into a useful concept for guiding research. Developing the common-sense notion that leisure lifestyles have time and space dimensions, Stebbins delves into distinctive leisure lifestyles which occur around particular free-time activities such as the serious ones where participants must routinely train, practice, rehearse, gather information, and those that are casual such as bingo, lunches with colleagues, and outings of small walking groups. Demonstrating the nuances of each, and analysing how serious activities are structured along the lines of the social world in which every lifestyle is embedded, this book revolutionises the idea of leisure lifestyle, turning it into a workable concept for guiding research, while also enriching our understanding of what it means. Striving to meet the test of a critical challenge in the field, this book is a refreshing new addition to the work on leisure, from a highly-respected and established scholar.